1998
DOI: 10.1046/j.1365-2141.1998.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of p55 and p75 soluble TNF receptors in adult acute leukaemia at diagnosis: correlation with clinical and biological features and outcome

Abstract: Summary. The tumour necrosis factor (TNF)/TNF-receptor (TNFR) complex plays a role in the growth of leukaemic cells. We retrospectively investigated the relationship between pretreatment serum concentration of soluble TNFR (p55-and p75-sTNFRs) and outcome in adult acute myeloid (AML 82 cases) and lymphoid (ALL 44 cases) leukaemia. Both sTNFRs were significantly higher in AML (p55-sTNFR 4 . 53 Ϯ 3 . 7, median 3 . 75; p75-sTNFR 6 . 51 Ϯ 5 . 25 ng/ml, median 4 . 72) and ALL sera (3 . 31 Ϯ 1 . 5, median 2 . 95; 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 30 publications
2
17
2
Order By: Relevance
“…In contrast to these findings, which underline the adverse prognostic impact of high sTNFRp55 levels previously reported for patients with other malignant diseases, 16,17 soluble TNFRp75, acting as competitive TNF␣, recently was used to treat patients with refractory hematologic malignancies. 32,33 In support of our observations, in those studies, patients who were treated with soluble TNFRp75 not only demonstrated no response to therapy but also experienced acceler- The mechanism of cleavage of membrane-bound receptor remains undefined in most instances.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In contrast to these findings, which underline the adverse prognostic impact of high sTNFRp55 levels previously reported for patients with other malignant diseases, 16,17 soluble TNFRp75, acting as competitive TNF␣, recently was used to treat patients with refractory hematologic malignancies. 32,33 In support of our observations, in those studies, patients who were treated with soluble TNFRp75 not only demonstrated no response to therapy but also experienced acceler- The mechanism of cleavage of membrane-bound receptor remains undefined in most instances.…”
Section: Discussioncontrasting
confidence: 52%
“…These results are in agreement with previous studies in patients with Hodgkin disease and AML. 16,17 The current findings lead us to assume that the generation of sTNFRp55 in excess may have the consequences of protecting malignant cells from cytotoxic activity and immunologic antitumor responses, thus facilitating their growth in vivo. This assumption is supported by previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EFS curves were estimated by the Kaplan-Meier method (30). In univariate analysis, we tested the following variables by log-rank test or, for continuous variables, Cox's proportional hazard regression model (31,32) INK4a were also considered together as a categorical variable (both < 30%, either <30%, both !30%) and compared by the log-rank test. In Supplementary Data, the primary cohort was further studied, including sCD30 (< or !…”
Section: Discussionmentioning
confidence: 99%
“…For RT-PCR, 4 g RNA was reverse-transcribed as previously described 41,42 and was cDNA amplified using the following primers: (1) CXCR4 sense 5Ј-AGAAC-CAGCGGTTACCATGGA-3Ј and antisense 5Ј-GAGTGTGACAGCTTG-GAGATG-3Ј (702 bp); (2) CCR1 sense 5Ј-GAAACTCCAAACACCACA-GAG-3Ј and antisense 5Ј-CAGCTTCCACTCTCGTAGGCTT-3Ј (588 bp); (3) CCR3 sense 5Ј-TCCTT CTCTCTTCCTATCAATC-3Ј and antisense 5Ј-GGCAATTTTCTGCATCTG-3Ј (313 bp); (4) CCR5 sense 5Ј-CGCAT-CAAGTGTCAAGTCCAATC-3Ј and antisense 5Ј-TG TAAACTGAGCTT-GCTCGCT-3Ј (1014 bp); (5) Vimentin sense 5Ј-GCTCAGATTCAGGAA-CAGCAT-3Ј and antisense 5Ј-TAAGGGCATCCACTTCACAGG-3Ј (266 bp). cDNAs were denatured for 5 minutes at 94°C before 35 runs at 58, 52, 57, and 60°C for 40, 30, 40, and 40 seconds, respectively (annealing) and at 72°C for 50 seconds (elongation) followed by 5 minutes at 72°C in a thermal cycler (GeneAmp PCR System 2400; PE Biosystems, Foster City, CA) using 1.25 U Taq polymerase (PE Biosystems) in 50 L. PCR products were separated by electrophoresis on 1.5% agarose gel.…”
Section: Northern Blot and Reverse Transcription-polymerase Chain Reamentioning
confidence: 99%